2018
DOI: 10.1272/jnms.jnms.2018_85-30
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Balneotherapy in Rehabilitation Medicine

Abstract: Balneotherapy is a treatment with healing waters, which includes bathing and physiotherapy in thermal water, therapeutic drinks, medical massage, and water jet massage. It is based on the buoyancy, physical properties, temperature, and chemical effects of mineral water. Throughout European and Japanese medical institutions, balneology and hot spring therapy is very much a part of routine medical treatment. The mechanism of balneotherapy is not yet completely understood. Balneotherapeutic procedures are mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 49 publications
0
25
0
5
Order By: Relevance
“…Balneotherapeutic treatments, through the use of natural factors, are based on the physical properties, temperature and chemical content of mineral water and mofette. The balneotherapeutic treatments have indications for chronic cardiac diseases, but additional data regarding their efficacy, safety and possible side effects are required (11).…”
Section: Discussionmentioning
confidence: 99%
“…Balneotherapeutic treatments, through the use of natural factors, are based on the physical properties, temperature and chemical content of mineral water and mofette. The balneotherapeutic treatments have indications for chronic cardiac diseases, but additional data regarding their efficacy, safety and possible side effects are required (11).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment choice as well as the risk assessment process must consider the nature of the water that supplies the pool plant [25]. In natural spa pools, indeed, the water should remain untreated because the claimed beneficial effects are supposed to derive from their unique chemical-physical properties [22,25] [11][12][13][14][15]54]. Based on the available version of the mfAtlas database and in according with the observations from other studies and the Earth Microbiome Project, the percentage of unknown species in is still high, covering about 10-70% of the spa water microbiota component [49,55].…”
Section: The Question About "Identity" and "Untouchability" Of Spa Anmentioning
confidence: 99%
“…The treatments with mineral thermal water or mud showed effective in pain relief and function restoration, impacting also on quality of life: several parameters of clinical interest, and other key issues were reported to play a role in several rheumatologic diseases e.g. : knee and hand osteoarthritis, chronic low back pain, rheumatoid arthritis, and osteoporosis) compared to baseline and non-mineral similar treatments [14][15][16]. The thermal waters and spas have ancient roots in history and still today represent a promising opportunity for physical and social well-being but require surveillance to assure appropriate hygiene standards to the final aim of reducing hazards and maximizing benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of the hot spring water therapy in functional improvements, musculoskeletal diseases, and rehabilitation of patients in sports medicine is well known [3]. Recent studies have indicated that the physical properties and chemical effects of this type of water have a potential application in immuno-inflammatory processes, chronic pain diseases, chronic cardiac procedures, metabolic syndromes and neurological illnesses [4]. The use of thermal waters in dermatology treatments provides therapeutic benefits due to their non-pathogenic microbes and mineral content.…”
Section: Introductionmentioning
confidence: 99%